2022
DOI: 10.1039/d1ta07186f
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-induced interfacial electronic structure of NiS2/CoS2with optimized water and hydrogen binding abilities for efficient alkaline hydrogen evolution electrocatalysis

Abstract: Fabricating heterostructures with dense interfacial catalytic sites is vitally essential for implementation of high-performance hydrogen evolution reaction (HER). However, the strong correlation between the adsorbed hydrogen atoms and electronegative nonmetal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…With the fast-growing development of electric devices and electrical power systems, polymer dielectrics with high power density and fast charge/discharge rates are particularly suited for modern electrical and electronic applications, such as high-frequency inverters, femtosecond lasers, and kinetic energy weapons. 1–4 However, the energy storage density of polymer dielectrics is generally low. For instance, the discharge energy density ( U e ) of biaxial polypropylene (BOPP) is only 2 J cm −3 at a high breakdown strength ( E b ) of ∼600 kV mm −1 , which makes it difficult to meet the demands of high energy storage equipment.…”
Section: Introductionmentioning
confidence: 99%
“…With the fast-growing development of electric devices and electrical power systems, polymer dielectrics with high power density and fast charge/discharge rates are particularly suited for modern electrical and electronic applications, such as high-frequency inverters, femtosecond lasers, and kinetic energy weapons. 1–4 However, the energy storage density of polymer dielectrics is generally low. For instance, the discharge energy density ( U e ) of biaxial polypropylene (BOPP) is only 2 J cm −3 at a high breakdown strength ( E b ) of ∼600 kV mm −1 , which makes it difficult to meet the demands of high energy storage equipment.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the H adsorption ability of non-metal sites in metal compounds is closely related to their p-band positions, namely the H bond strength increases as the p-band center of the non-metal is upshifted relative to the Fermi level. 56–58 As shown in Fig. 8g, the p-band of Se increases from −2.10 to −1.92 eV after Se enrichment, suggesting that the H adsorption at Se sites can be effectively strengthened to form a reinforced Se–H ads bond.…”
Section: Resultsmentioning
confidence: 88%
“…The high combustion heat value, clean combustion products, and abundant resources make hydrogen (H 2 ) a distinguished energy storage material. Producing hydrogen from the electrochemical decomposition of water (H 2 O), the commonly believed future energy carrier, 1,2 through hydrogen evolution reaction (HER) has been proved to be a clean and renewable method. However, the hydrogen production catalyst precious metal platinum (Pt), the most efficient electrocatalyst for HER owing to its high stability, low overpotential (about 0.08 V), as well low Tafel slope, 3 has not been applied on large scales due to its high cost and scarcity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, transition metal sulfides (TMSs), such as MoS 2 , 4–10 VS 2 , 11–15 CoS 2 , 2,16–20 NiS 2 (ref. 2, 7, 15, 21 and 22) have been attracting attention from researchers and industry practitioners.…”
Section: Introductionmentioning
confidence: 99%